ESTIMASI KANDUNGAN KARBON TEGAKAN HUTAN DI ATAS PERMUKAAN TANAH PADA BERBAGAI KELAS TUTUPAN TAJUK DI HUTAN ADAT PENGAJIT KABUPATEN BENGKAYANG - Kasianus, Robi; Astiani, Dwi; AM, Iskandar (JURNAL HUTAN LESTARI, 2018)
Forests are the largest component that is able to absorb carbon through photosynthesis process and store carbon in forests biomass per unit area. The aim of this study was to estimate the carbon that stored in above ground forest in Pengajit customary forest of Bengkayang regency. The method used in this study was non destructive by surveying the diameter and the species of forest. The results of this study showed that carbon stock of above groud forest in Pengajit customary forest was vary on each canopy cover class. The biggest carbon found at the dense canopy cover class was 299,74 tons/ha, and the medium canopy cover class had 235,67 tons/ha carbon stock, while the smallest carbon stock value was 55,89 tons/ha at the lowest canopy cover class. Total carbon stocks that found at the dense conopy cover class was 26.124,19 tons, the medium canopy cover class stored 1.397,53 tons, and the lowest canopy cover class had 428,25 tons. Pengajit customary forest as a whole saved 27.949,97 tons carbon stocks.Keywords : Canopy cover class, carbon stock, customary forest, forest stand